Case Report of Gastrointestinal Bleeding in an Adult with Chronic Visceral Acid Sphingomyelinase Deficiency. (4th April 2019) - Cassiman, David; Libbrecht, Louis; Meersseman, Wouter; Wilmer, Alexander
Abstract : Introduction . Acid sphingomyelinase deficiency (ASMD, also known as Niemann-Pick Type A and Type B disease) is a rare, inherited metabolic disorder. Liver-related issues, including cirrhosis and variceal haemorrhage, are a leading cause of early mortality in individuals with chronic forms of ASMD. Due to the rarity of this lysosomal storage disorder, there can be a lack of awareness that adults with chronic ASMD disease are at significant risk of cirrhosis, portal hypertension, and variceal bleeding. This case highlights an unusual presentation of recurrent variceal bleeding in an adult with cirrhosis and portal hypertension due to chronic visceral ASMD. Case Presentation . A patient with severe splenomegaly was diagnosed with ASMD at age of 25. At age 64 they had multiple hospital admissions for hematochezia (originally diagnosed as ischemic colitis) accompanied by hypotension (blood pressure 91/45 mmHg), anemia (hemoglobin 8.5g/dL, ref 12-16; INR 1.4, ref ≤1.2), and mild renal insufficiency (creatinine 1.33mg/dL, ref 0.51-0.95). Colonoscopy did not reveal a source of bleeding. Computerized tomography scanning imaging showed diffuse venous collaterals and ascites. Arteriographies during subsequent episodes of bleeding were negative for active arterial intestinal bleeding. Recurrent gastrointestinal bleeding was found to originate from a varicose vein cluster connected to the right iliac vein and the superior mesenteric vein, located in the submucosa of a small intestinal loop. Multiple varices were secondary to portal hypertension in the context of cirrhosis. The patient died from recurrent variceal bleeding that exacerbated liver failure worsened by pneumonia and hypovolemic and septic shock. Conclusions . The variceal bleeding in this patient was atypical in that it originated from venous collaterals bleeding into the small intestine rather than the more typical gastroesophageal varices observed in ASMD. With long standing liver dysfunction and gradual development of portal hypertension, intestinal varices rather than occult intestinal bleeding due to ischemia should be considered in ASMD patients presenting with either hematochezia or hematemesis.